Comparison of Fourier-Domain and Time-Domain Optical Coherence Tomography in the Measurement of Thinnest Corneal Thickness in Keratoconus - Chunxiao Wang; Xueying Xia; Bishan Tian; Shiyou Zhou (Journal of Ophthalmology)
Objective. To compare fourier-domain optical coherence tomography (FD-OCT) and time-domain OCT (TD-OCT) in the determination of thinnest corneal thickness (TCT). Methods. This study included 55 keratoconus patients and 50 healthy volunteers. The RTVue-OCT (FD-OCT) and Visante-OCT (TD-OCT) were used for the measurement of the TCT. Three consecutive scans were performed. The comparison and agreement between the two modalities were analyzed by paired t-test, the Pearson correlation, intraclass correlation coefficient (ICC), and Bland-Altman plots. intraobserver repeatability was analyzed by the intraobserver within-subject standard deviation (S(w)), coefficient of variation (CV(w)), and ICC. Results. The TCT value of normal corneas was higher by RTVue-OCT (530.4 ± 19.7 μm) than Visante-OCT (521.5 ± 18.3 μm) (p<0.001). For keratoconus eyes, the TCT was 425.0 ± 58.2 μm and 424.4 ± 55.7 μm (difference being 0.6 ± 10.2 μm, p=0.604). Strong correlation (r = 0.938∼0.985) (ICC = 0.915–0.984) was observed between the two OCTs, and each OCT exhibited excellent repeatability in determining the TCT in all subjects (ICC = 0.984–0.994). Conclusions. The values of TCT obtained from RTVue-OCT and Visante-OCT were highly correlated; however, the two values were different. Both OCT instruments exhibited good intraobserver reliability. The existence of systematic differences suggested that the two instruments cannot be used interchangeably.